Reliability of Mandibular Plane in Determining Gonial Angle on Lateral Cephalogram: Mandibular Plane in Gonial Angle on Lateral Cephalogram - Mustafa, Maleeha; Shafique, Asma; Syed, Abir Arif (Pakistan Journal of Health Sciences, 2025)
Gonial angle is an essential cephalometric indicator used in orthodontic diagnosis and treatment planning. The precise evaluation of the gonial angle is vital for understanding mandibular growth patterns and formulating efficient treatment strategies. Objectives: To assess the mean gonial angle according to the three mandibular planes, Tweed's, Steiner's, and Down's, on lateral Cephalogram and panoramic radiograph for Orthodontic Diagnosis and Treatment Planning. Methods: The Descriptive Cross-Sectional Survey was performed in the Orthodontics Department, Lahore Medical and Dental College (LMDC). Lateral Cephalogram and Ortho-pantomography (OPG) of 100 patients were used. The Gonial angle was assessed on the OPG by drawing a tangent to the lower border of the mandible and the most distal point of the ascending ramus and condyle. On the Lateral Cephalogram, however, the Gonial angle was measured by drawing a tangent to the posterior border of the ramus and making three mandibular planes according to Down, Tweed, and Steiner analysis. The Gonial angle assessed on the lateral Cephalogram was compared to that on OPG to evaluate which plane provides the gonial angle value closest to that obtained on OPG. All data were collected and recorded on a Performa. Results: The mean gonial angle on lateral Cephalogram was 123.06 ± 6.80º, 121.5 ± 6.40, and 123.77 ± 6.43 using Tweeds, Steiner's, and Downs mandibular planes, respectively, and on OPG, the mean gonial angle was 123.45 ± 6.89. Conclusions: It was concluded that Down’s mandibular plane provides the Gonial angle reading that is closest to that found on OPG.